A dynamic landscape of allergen associations in delayed‐type cutaneous hypersensitivity. (1st January 2017) - Lynch, M.D.; White, J.M.; McFadden, J.P.; Wang, Y.; White, I.R.; Banerjee, P.
Summary: Background: Delayed‐type hypersensitivity represents a significant clinical and public health challenge. Patients undergoing patch testing may exhibit positive reactions to more than one allergen. It is recognized that reactions to specific pairs of allergens are associated, reflecting a combination of exposure patterns and structural similarity. Objectives: To explore the influence of time of testing, age, sex and atopy status on allergen pair associations in a series of 45 110 consecutive patients tested over 30 years. Methods: Patch test records of all patients undergoing testing with a modified European baseline series between 1985 and 2014 were retrieved from a database at St John's Institute of Dermatology. Reactions were read on days 2 and 4. For each allergen it was recorded whether the allergen was tested and whether the result was positive or negative. Results: This is the largest reported study of patch test allergen pair relationships. Our analysis shows a high degree of variability in allergen pair associations. Rigorous statistical analysis reveals a large number of differences between groups, including a significant increase in the association between formaldehyde and multiple formaldehyde‐releasing preservatives over the study period, in addition to pair associations with cobalt and formaldehyde‐releasing preservatives. These were present to a significantly greater extent in men than in women. Conclusions: These observations extend our understanding of cutaneous allergy, with implications for both clinical practice and mechanisms of cutaneous hypersensitivity.